SEPARABLE AND INSEPARABLE TRANSITIVE PHRASAL VERBS - Diana Anggraeni; Cece Sobarna; Lia Maulia; Eva Tuckyta Sari Sujatna (Faculty of Social and Political Sciences University of Bangka Belitung, 2020)
A phrasal verb is a phrase consisting of standard verbs and one or two particles. The standard verb is like go, make, take. While the particles (s) used can be within the form of adverbs and/ or prepositions. Usually, a phrasal verb is often used in native-speaker dialogue and informal English writing. The purpose of this study is to describe transitive phrasal verbs. The method used in this research is a descriptive qualitative method. Linguistic data sources were taken from the British National Corpus. Data containing phrasal verbs are collected and then classified into several categories. Categories that are suitable for research purposes are separated and labeled and then explained in the narrative in accordance with the theory and research objectives. The results showed that transitive phrasal verbs consist of two types, namely separable and inseparable transitive phrasal verbs. A separable transitive phrasal verb is a type of phrasal verb whose particles are separated from the verb and inserted by the noun phrase as its object. In addition, particles must be separated from the verb if the object used is in the form of a pronoun. While inseparable transitive verbs are phrasal verbs that have a direct object but the particles are inseparable from the verb.